Academic Procrastination among College Students: Do Self-Efficacy and Social Support Matter? - Viona Nada; Eko Sujadi; Betaria Putra (EduLine: Journal of Education and Learning Innovation, 2024)
Academic procrastination, a common behavior among university students, is concerning due to its potentially adverse impact on their academic performance. This study aims to explore the impact of self-efficacy and social support on academic procrastination. Employing a quantitative approach with a survey design, 120 students were selected using a convenience sampling technique. Data collection involved self-efficacy, social support, and academic procrastination scales, analyzed through descriptive statistics, simple regression, and multiple regression. The findings indicated low levels of academic procrastination, with self-efficacy and social support falling within moderate ranges. Hypothesis testing demonstrated the partial influence of self-efficacy and social support on academic procrastination. Simultaneous testing confirmed the combined impact of self-efficacy and social support on academic procrastination. This study underscores the significance of counseling services in higher education to address and mitigate academic procrastination by enhancing social support and self-efficacy. Future research should consider testing a more intricate structural model involving additional variables that may directly or indirectly affect academic procrastination.